1981
DOI: 10.1210/jcem-53-4-813
|View full text |Cite
|
Sign up to set email alerts
|

Human Cord Blood Concentrations of Thyrotropin, Thyroglobulin, and Iodothyronines after Maternal Administration of Thyrotropin-Releasing Hormone*

Abstract: TRH or saline was administered to 214 term pregnant women at various time intervals (8-820 min) before delivery. Cord blood (CB) was obtained, and plasma TSH, T4, T3, rT3, and thyroglobulin concentrations were measured by specific RIA. CB TSH was significantly elevated within 20 min after TRH administration and remained elevated for 180 min. CB T3 rose significantly by 60 min and remained elevated for 820 min. CB T4 was significantly increased from 120 to 820 min after TRH administration. There was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…This brisk TSH response seen in our hyperbilirubinaemic newborns immediately after exchange transfusion has to our knowledge not been shown previously and is similar to that seen in our control population of healthy newborns after TRH stimulation, as well as to that reported in other studies in healthy newborns [2,6,16]. These results indicate that hyperbilirubinaemic newborns undergoing exchange transfusion are capable of responding adequately to acute TRH stimulation and have an intact pituitary-thyroidal axis.…”
Section: Discussionsupporting
confidence: 91%
“…This brisk TSH response seen in our hyperbilirubinaemic newborns immediately after exchange transfusion has to our knowledge not been shown previously and is similar to that seen in our control population of healthy newborns after TRH stimulation, as well as to that reported in other studies in healthy newborns [2,6,16]. These results indicate that hyperbilirubinaemic newborns undergoing exchange transfusion are capable of responding adequately to acute TRH stimulation and have an intact pituitary-thyroidal axis.…”
Section: Discussionsupporting
confidence: 91%
“…The relative independence of this aspect of lung development from any fixed developmental program and its ability to respond to hormones at a very early stage of gestation may be important factors in determining the severity of respiratory disease in those very small preterm infants who have had insufficient prenatal exposure to T3 and hydrocortisone. Since cortisol and T3 concentrations can be manipulated both pre- (27,28) and postnatally, it may be possible to use these hormones to enhance the lung liquid reabsorptive capacity of the immature lung. seen during this part~of gestation (4) rather than a T3/hydrocoT-5.…”
Section: Hormone Concentrations and Timing Of Reabsorptive Responsementioning
confidence: 99%
“…(18) also found that maternal administration of TRH resulted in peak fetal serum TSH values 40-60 min after the infusion; thereafter serum TSH showed a steady decline. Maximal stimulation of the fetal thyroid occurred about 2 h after the maternal injection of TRH.…”
Section: ------------------------- Tmentioning
confidence: 76%
“…Intraamniotic injection of thyroid hormones, however, does result in higher fetal levels (33). TRH, on the other hand, crosses the placenta readily and stimulates the fetal pituitary (16)(17)(18).…”
Section: ------------------------- Tmentioning
confidence: 99%
See 1 more Smart Citation